Socioeconomic Disparities in Smoking Behavior and Early Smoking Initiation Among Men in Malawi - Yaya, Sanni; Bishwajit, Ghose; Shah, Vaibhav; Ekholuenetale, Michael (Université d'Ottawa | University of Ottawa, 2017)
Tobacco smoking is a growing concern for health care systems as it is projected to become the leading cause of death in the developing world. Knowledge of how smoking behavior differs across socioeconomic groups is crucial for designing effective preventive policies and alleviating the disparities. The aim of this study was to report the prevalence of (1) smoking status, (2) early smoking initiation, and (3) association with socioeconomic status (SES) of the 2 among Malawian men.
Keywords: Age of initiation; Malawi; men; smoking; socioeconomic status